Repeatability of the Universiti Teknologi MARA reading charts (Bangladesh Journal of Medical Science, 2015)
Objective: This study was done to investigate the repeatability measurements in reading rate using the Universiti Teknologi MARA Malay related words (UiTM-Mrw) reading chart and Universiti Teknologi MARA Malay unrelated words (UiTM-Muw) reading chart. Methodology: Thirty normally sighted participants were randomly recruited through randomised sampling (mean age =21.5±1.1 years). Participants were instructed to read aloud, clearly and as quickly as possible at 2 different sessions using two different charts. The two charts were selected at random sequence. A minimum of 7 days interval was used to minimize the learning affect. The time taken to read each chart was recorded and any errors while reading was noted. Reading performance was quantified as reading rate in words per minute (wpm). Results: Comparison of reading rate between session 1 and session 2 was not significantly different (p=0.894, df=1, F=0.018) for UiTM-Mrw reading chart. The reading rate between session 1 and 2 also showed no significant difference (p=0.99, df=1, F=2.811) in UiTM-Muw reading chart. Intra-class correlation coefficient (ICC) showed a good consistency in repeatability for both UiTM-Mrw reading chart and UiTM-Muw reading chart with ICC values of 0.849 and 0.814 respectively. The Bland and Altman plot between measurement of reading rate in session 1 and session 2 showed a good agreement in UiTM-Mrw reading chart and UiTM-Muw reading chart. Conclusion: Both UiTM-Mrw reading chart and UiTM-Mur reading chart showed a good consistency and good agreement in repeated measurement of reading rate.Bangladesh Journal of Medical Science Vol.14(3) 2015 p.236-240